Tata Laku, Tata Nilai dan Sistem Spasial pada Hunian Masyarakat Peladang Jagung di Madura Timur - Redi Sigit Febrianto; Fifi Damayanti (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2020)
The identity of the Madurese ethnic community, especially in the eastern part, is known as a devout Muslim community as well as a corn farming community. This is reflected in the values ​​and practices and the spatial system. This research is different because it tries to explore the relationship between the practices, values ​​, and spatial systems of the farming community in eastern Madura. Exploration of the spatial system starting from the landscape area, yard area to the residential area. The aim is to form a descriptive narrative about the relationship between values, behavior, and the spatial system of the maize farming community in East Madura. The theoretical study of the spatial system (object) in this study refers to the landscape-settlement concept from Kusdiwanggo and the habitat concept from Egenter. The theoretical study of the farming community (subject) refers to the concept of behavior and values ​​from the Boelaars. The research design is qualitative, the data is not numerical. The research strategy is descriptive type, namely trying to explore narrative data. The data collection method uses focused interviews and field observations. Validated with field sketches and field documentation. In-depth interviews use a semi-structured interview type. The data analysis method used is inductive, where the results are in the conclusion section. The conclusion of this research is that the spatial system, values ​​, and behavior of the farming community in East Madura are based on Islam.